Impact factors and dynamic simulation of tillage-layer temperature in frozen-thawed soil under different cover conditions - Fu, Qiang; Ma, Zi’ao; Wang, Enliang; Li, Tianxiao; Hou, Renjie (International Journal of Agricultural and Biological Engineering, 2018)
Based on a winter field experiment between 2016 and 2017, four treatments (bare land (BL), natural snowfall coverage (NS), 5-cm-deep straw + natural snowfall coverage (SC5), and 10-cm-deep straw + natural snowfall coverage (SC10)) were established to determine the effects of the different treatments on soil temperature at the soil surface and at depths of 10 cm, 20 cm, and 30 cm. The environmental factors of ambient temperature, ambient humidity, water vapor pressure, 10-min wind speed, total radiation, net radiation, and long wave radiation were obtained from the weather station in the study area. Through correlation, multiple regression, and stepwise regression analysis, models for dynamic simulation of the tillage-layer soil temperature were constructed for analyzing the relation between tillage-layer soil temperature and environmental factors. The results showed that the environmental factors were all significantly correlated with tillage-layer temperature at the 0.01 level; when the impacts of other environmental factors were excluded, the correlations decreased significantly. The dynamic simulation models for tillage-layer soil temperature under different coverage conditions were different, and the larger the coverage amount, the fewer the environmental factors that could affect the tillage-layer temperature. The coefficients of determination of the prediction results of the dynamic models for the tillage-layer soil temperature under the four treatments (BL, NS, SC5, and SC10) were 0.8385, 0.7110, 0.7283, and 0.6216, respectively. The prediction had a high accuracy and can accurately depict the dynamic changes of the tillage-layer soil temperature. The results provided a theoretical basis for the efficient utilization of farmland soil water and heat resources. Keywords: farmland cover condition, frozen-thawed soil, tillage-layer temperature, impact factor, dynamic simulation, stepwise regression DOI: 10.25165/j.ijabe.20181102.3068 Citation: Fu Q, Ma Z A, Wang E L, Li T X, Hou R J. Impact factors and dynamic simulation of tillage-layer temperature in frozen-thawed soil under different cover conditions. Int J Agric & Biol Eng, 2018; 11(2): 101–107.